Sosialisasi Literasi Keuangan Melalui Edukasi Menabung Sejak Dini Sebagai Wujud Perencanaan Finansial di Bogor, Jawa Barat - Tyahya Whisnu Hendratni; Shinta Budi Astuti; Ateniyanti Ateniyanti (LPMP Imperium, 2023)
A sign that a region is progressing is the economic independence of its people. However, many people are unaware of this potential, so we need motivation-based community empowerment efforts. This will encourage people to develop the local economy in their area. Saving money is an essential part of managing finances to achieve your goals. Keeping money can also help the community, especially children, to develop the economy in their village. By teaching children about financial planning early on, they can understand the benefits of accessing financial services and facilities, including savings. The implementation process has several stages: preparation, evaluation, and reporting. The results of these activities were excellent, and they went according to plan. Hopefully, these efforts will encourage younger generations in Indonesia to develop the habit of saving, ultimately benefiting the nation and the state.